Regulation of Expression of CXC Chemokines in Cultured Hepatocytes - GhH Hassanshahiraviz; AJ Dickson (Tehran University of Medical Sciences, 2005)
Chemokines are low molecular weight proteins (8-17 kDa). They are classified in four distinct groups as CXC, CC, CX3C and C. Depending on the presence or absence of a motif called ELR (Arg-Leu-Glu) before the first cysteine residue in their structure, CXC chemokines are also subdivided into ELR+ and ELR-. Increasing evidence has indicated the existence of a chemokine network in the liver which is involved in both physiological responses and, under certain circumstances, pathological and repair processes following hepatic injury. The CXC chemokines play a major role in both these processes, and much attention has been focused on their therapeutic applications to liver disease. However, whilst non-parenchymal cells represent a major source of chemokines, the secretion and role of hepatocyte-derived CXC chemokines in these processes is largely unknown. The responses of hepatocytes to the stress imposed during isolation by collagenase perfusion are thought to mimic those that the liver experiences after injury in vivo, such as during stress, trauma or after insults, and therefore provides a useful model to study the regulation of expression of these chemokines in vitro. The present study shows that the ELR- CXC chemokine, SDF-1, and the ELR+ chemokine, Gro/KC, are secreted from isolated rat hepatocytes immediately after isolation and early during culture. Two other chemokines IP-10/Mob-1 and IL-8/MIP-2 exhibited inducible expression, with IP-10/Mob-1 reaching maximal expression within 3h of cell isolation with a slightly delayed maximal expression (5h) for IL-8/MIP-2. The pro-inflammatory cytokines, TNF- and IFN-, selectively stimulated expression of IP-10/Mob-1 but were without effect on Gro/KC. IP-10/Mob-1, SDF-1 and Gro/KC expression by hepatocytes was stimulated in response to heat shock but only IP-10/Mob-1 expression increased in response to FCS, medium additives or maintenance of cells in suspension culture. The expression of the CXC chemokines IP-10/Mob-1 and Gro/KC was inhibited in the presence of inhibitors of specific protein kinases and signal pathways- SB203580, MG132, KN62 and Staurosporine. Expression of chemokines from isolated hepatocytes not only provides a useful model to study the induction of specific genes under stressful situations, but may also be beneficial in the development of therapeutic drugs that may regulate the pathological and regenerative processes that occur during, and following, liver disease.